Environmental Factors and Mulching Effects on Soil Nitrogen in Organic Curly Chili (Capsicum annuum L.) Cultivation for Sustainable Agriculture - Indah Retno Wulan; Bayu Dwi Apri Nugroho; Chandra Setyawan; Jeane Claudea Tanjung; Aristya Ardhitama (The University of Lampung, 2025)
Nitrogen availability is a critical determinant of chili yield, and its dynamics are influenced by environmental conditions and cultivation practices such as mulching. This study aimed to evaluate the combined effects of environmental factors and mulching on soil nitrogen levels in curly chili (Capsicum annuum L.) cultivation using organic fertilizer under a sustainable agriculture framework. The experiment used a randomized block design with 24 plots and three treatments: no mulch (P1M0), organic mulch with bamboo leaves (P1M1), and inorganic mulch with plastic (P1M2). Monitoring was conducted for 4 months on soil pH, volumetric water content (VWC), electrical conductivity (EC), temperature, rainfall, solar radiation, humidity, and wind speed. Results showed that soil nitrogen was highest in no mulch (31.1 mg/kg), followed by organic mulch (28.8 mg/kg), and lowest in inorganic mulch (25.6 mg/kg). ANOVA confirmed that organic mulch was comparable to no mulch, but significantly better in maintaining nitrogen than inorganic mulch. Regression analysis identified electrical conductivity as the strongest positive predictor across all treatments, while soil pH showed negative effects and average temperature tended to reduce nitrogen under no mulch conditions. Model accuracy was strong (R²: P1M0 = 0.799, P1M1 = 0.799, P1M2 = 0.699). The use of bamboo leaves can be an alternative in maintaining soil nitrogen availability. Mulching practices adapted to environmental conditions can enhance soil fertility and support sustainable chili production.